Sheikh Mohammed Khiabani Social-philosophical and Socio-political Views - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2019)
The article analyzes the socio-philosophical and socio-political views of Sheikh Mohammed Khiabani. The author here shows that, the Khiabani’s sociophilosophical views are based on renovation and beginning of a new cultural phase. The article also notes that Khiabani worked on the philosophy of individual and society interdependence, that is, the common spirit of individuals, coming together in a collective way. According to this philosophy, individuals have always been the “conscience of the people” to save them from enslavement and misery. In this sense, to keep the “conscience of the people” alive at all times, faults should be noted when necessary. According to Khiabani, showing the faults and disadvantages of any nation can either degrade or raise it. The article also shows that supressing personal fears and slavery and choosing martyrdom for the sake of nation and homeland is the basis of Khiabani’s philosophy. As the author of this idea, he died for the freedom of his homeland and nation. Thus, the idea of freedom of individuals and society is the key point in Khiabani’s sociopolitical views. The article describes Khiabani’s active struggle for social and political ideas (national freedom, human freedom, national culture, and secular culture) in detail. Specifically, the article explored the struggles of the South Azerbaijani people during the recession of the Qajar state and Khiabani’s special role in this struggle.